OPTIMIZING CHILDREN GROSS MOTORIC SKILL BY YOGA ASANA PRACTICE IN COVID-19 PANDEMIC - Ni Putu Eni Astuti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This paper describes the activity of yoga asana in optimizing children gross motoric skill. It is a qualitative descriptive study involving early age children in Buahan Village, Bali in Yoga Asana as an activity to improve physical activity in covid-19 pandemic. The data source used primary and secondary data sources. The primary data source was collected from the result of observation and interview regarding to Asana’s systematic and sequences. The secondary data was collected from yoga literature review and research review, especially yoga for the children. Data analysis used content analysis about child muscle activity in every Asana in every steps of Yoga Asana. The finding showed that Yoga Asana activity consisted of five steps namely asana stretching, the core of asana, relaxation, pranayama, and simple meditation. From these sequences, asana stretching and the core of asana could the most optimize the child gross motoric performance by (1) improving child movement range through joint movement, (2) improving physical activity performance by preparing muscle, train muscular flexibility behind the knee, strengthening muscles of arms, back, stomach, shoulders and legs, (3) improving flexibility and align the spinal nerves, (4) improving movement coordination of the child body.